Non-aqueous electrolyte secondary batteries and the electrolytes used therein

By adding LFSI and isopropyl acetate to the electrolyte solution of the nonaqueous electrolyte secondary battery, the problem of reduced capacity of the battery during long-term circulation is solved, and better cycle characteristics are achieved.

CN113366686BActive Publication Date: 2025-03-04PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080011090.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-31
Filing Date
2020-01-06
Publication Date
2025-03-04
Estimated Expiration
2040-01-06

AI Technical Summary

Technical Problem

The capacity of nonaqueous electrolyte secondary batteries is easily greatly reduced during long-term repeated charge and discharge cycles.

Method used

The lithium salt lithium bis(fluorosulfonyl)imide (LFSI) and isopropyl acetate were added to the electrolyte. The lithium salt contained an LFSI coating, and the content of isopropyl acetate was controlled below 1000 ppm to inhibit the excessive reaction of LFSI on the positive electrode surface.

Benefits of technology

The combination of LFSI coating and isopropyl acetate effectively suppresses the reduction of capacity during the charge and discharge cycle and improves the long-term cycle characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113366686B_ABST
    Figure CN113366686B_ABST
Patent Text Reader

Abstract

A non-aqueous electrolyte secondary battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte comprises a lithium salt and isopropyl acetate, the lithium salt comprises lithium bis(fluorosulfonyl)imide, and the content of isopropyl acetate in the electrolyte is less than 1000 ppm relative to the mass of the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention mainly relates to the improvement of electrolyte for non-aqueous electrolyte secondary batteries. Background Art

[0002] Non-aqueous electrolyte secondary batteries, especially lithium ion secondary batteries, have high voltage and high energy density, and therefore are expected to be used as power sources for small household applications, power storage devices, and electric vehicles. In order to extend the life of the battery, it has been proposed to add lithium bis(fluorosulfonyl)imide to the electrolyte (Patent Documents 1 and 2).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2014 / 157591

[0006] Patent Document 2: International Publication No. 2016 / 009994 Summary of the invention

[0007] However, when the battery is repeatedly charged and discharged for a long period of time, its capacity may decrease significantly.

[0008] In view of the above, one aspect of the present invention relates to a non-aqueous electrolyte secondary battery, which has a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte comprises a lithium salt and isopropyl acetate, the lithium salt comprises lithium bis(fluorosulfonyl)imide, and the content of the isopropyl acetate in the electrolyte is less than 1000 ppm relative to the mass of the electrolyte.

[0009] Another aspect of the present invention relates to an electrolyte for a non-aqueous electrolyte secondary battery, comprising a lithium salt and isopropyl acetate, wherein the lithium salt comprises lithium bis(fluorosulfonyl)imide, and the content of the isopropyl acetate is 50 ppm or more and 1000 ppm or less by mass.

[0010] According to the present invention, a non-aqueous electrolyte secondary battery having excellent long-term cycle characteristics can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is a partially cutaway schematic perspective view of a nonaqueous electrolyte secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION

[0012] The non-aqueous electrolyte secondary battery of the present invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte comprises a lithium salt and isopropyl acetate. The lithium salt comprises lithium bis(fluorosulfonyl)imide: LiN(SO2F)2. The content of isopropyl acetate in the electrolyte is less than 1000 ppm relative to the mass of the electrolyte.

[0013] Lithium bis(fluorosulfonyl)imide (hereinafter also referred to as LFSI) forms a coating (hereinafter also referred to as LFSI coating) on ​​the positive and negative electrode surfaces that has excellent lithium ion conductivity and suppresses oxidative decomposition of the electrolyte. The LFSI coating suppresses the decrease in the initial capacity retention rate of the charge and discharge cycle.

[0014] On the other hand, when the battery is repeatedly charged and discharged for a long time, LFSI reacts excessively on the positive electrode surface, and the LFSI film becomes inert, thereby increasing the resistance and significantly reducing the capacity.

[0015] Isopropyl acetate has the effect of suppressing the excessive reaction of LFSI on the positive electrode surface. In particular, when the positive electrode contains a positive electrode material or a positive electrode active material that may contain an alkaline component such as a composite oxide containing lithium and nickel, the effect of suppressing the excessive reaction of LFSI is significant.

[0016] Isopropyl acetate generates alkoxy radicals in the battery, for example, by a reaction such as the following reaction formula (1). It is believed that the alkoxy radicals are adsorbed on the surface of the positive electrode material to form a protective layer that inhibits the reaction of LFSI on the positive electrode surface (for example, the reaction of LFSI with an alkali component). As a result, it is speculated that the inertization of the LFSI coating is suppressed and the reduction in capacity is also suppressed. That is, the capacity retention rate is improved when the battery is repeatedly charged and discharged for a long time.

[0017] Reaction formula (1): Me-CO-O-CH(Me)2+Li+HF

[0018] →Me-CO-H+·O-CH(Me)2(alkoxy radical)+LiF

[0019] The isopropyl acetate contained in the electrolyte needs to be a trace amount. When the amount of isopropyl acetate is excessive, isopropyl acetate itself forms a high-resistance film on the surface of the positive electrode. Therefore, the content of isopropyl acetate in the electrolyte needs to be 1000 ppm or less relative to the mass of the electrolyte, and can be 500 ppm or less, and 200 ppm or less is also sufficient.

[0020] During repeated charge and discharge cycles, isopropyl acetate is gradually consumed by reactions such as reaction formula (1). Therefore, in order to maintain the effect of isopropyl acetate even when the charge and discharge cycles of the battery are repeated for a long time, the electrolyte before the battery is injected or the electrolyte recovered from the battery at the beginning of use needs to contain a sufficient amount of isopropyl acetate. The electrolyte before the battery is injected or the electrolyte recovered from the battery at the beginning of use may contain, for example, 50 ppm or more of isopropyl acetate relative to the mass of the electrolyte, and the content of isopropyl acetate may be 100 ppm or more. At this time, when the electrolyte contained in the battery circulating in the market is analyzed, it is generally believed that isopropyl acetate above the detection limit remains.

[0021] The content of isopropyl acetate in the electrolyte solution can be measured by analyzing the electrolyte solution using gas chromatography, for example.

[0022] When isopropyl acetate is consumed, as a result, a LFSI film derived from LFSI and isopropyl acetate is formed at least on the surface of the positive electrode. Even if isopropyl acetate is not detected in the electrolyte in the battery, when a film derived from LFSI and isopropyl acetate is present at least on the surface of the positive electrode, this embodiment is also included in the present invention.

[0023] The concentration of the lithium salt in the electrolyte is preferably 1 mol / liter or more and 2 mol / liter or less, more preferably 1 mol / liter or more and 1.5 mol / liter or less. By controlling the lithium salt concentration to the above range, an electrolyte having excellent ion conductivity and moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.

[0024] In addition to LFSI, the lithium salt may also contain lithium hexafluorophosphate: LiPF6. In this case, the proportion of LFSI in the lithium salt is preferably 1 mol% or more and 60 mol% or less, more preferably 20 mol% or more and 60 mol% or less, and further preferably 30 mol% or more and 60 mol% or less. By including LiPF6 in the lithium salt, the quality of the LFSI coating is improved, and the capacity retention rate in the long-term cycle test can be more significantly improved.

[0025] The lithium salt may contain other salts in addition to LFSI and LiPF6, and the total amount of LFSI and LiPF6 in the lithium salt is preferably 80 mol% or more, more preferably 90 mol% or more. By controlling the ratio of LFSI and LiPF6 to the above range, it is easy to obtain a battery with better long-term cycle characteristics.

[0026] Next, the nonaqueous electrolyte secondary battery according to the embodiment of the present invention will be described in detail. The nonaqueous electrolyte secondary battery includes, for example, the following negative electrode, positive electrode, and nonaqueous electrolyte.

[0027] [negative electrode]

[0028] The negative electrode, for example, comprises a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector and containing a negative electrode active material. The negative electrode mixture layer can be formed by applying a negative electrode slurry formed by dispersing a negative electrode mixture in a dispersion medium on the surface of the negative electrode current collector and drying it. The dried coating film can also be rolled as needed. The negative electrode mixture layer can be formed on one surface of the negative electrode current collector or on both surfaces.

[0029] The negative electrode mixture contains a negative electrode active material as an essential component, and may contain a binder, a conductive agent, a thickener, etc. as an optional component. The negative electrode active material contains a material that electrochemically absorbs and releases lithium ions. As the material that electrochemically absorbs and releases lithium ions, carbon materials, Si-containing materials, etc. can be used. As Si-containing materials, silicon oxide (SiO x : 0.5≤x≤1.5), a composite material containing a silicate phase and silicon particles dispersed in the silicate phase, etc.

[0030] As carbon materials, graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon) can be exemplified. Among them, graphite with excellent charge and discharge stability and low irreversible capacity is preferred. Graphite refers to a material having a graphite-type crystal structure, including natural graphite, artificial graphite, and graphitized mesophase carbon particles. One carbon material can be used alone, or two or more can be used in combination.

[0031] Among the negative electrode active materials, for the composite material containing a silicate phase and silicon particles dispersed in the silicate phase, the content of silicon particles can be arbitrarily selected, so it is easy to achieve high capacity. Here, the silicate phase refers to a composite oxide phase containing silicon, oxygen, alkali metals, etc. In the following, the composite material in which the silicate phase is a lithium silicate phase containing silicon, oxygen and lithium is also referred to as "LSX". The higher the content of silicon particles in LSX, the greater the negative electrode capacity. LSX absorbs lithium ions by alloying silicon and lithium. By increasing the content of silicon particles, high capacity can be expected. The lithium silicate phase preferably has a composition formula of Li y SiO z (0<y≤8, 0.5≤z≤6). It is more preferable to use the composition formula Li 2u SiO 2+u As shown in (0<u<2).

[0032] The crystallite size of the silicon particles dispersed in the lithium silicate phase is, for example, greater than 5 nm. The silicon particles have a granular phase of a silicon (Si) single substance. When the crystallite size of the silicon particles is set to be greater than 5 nm, the surface area of ​​the silicon particles can be suppressed to be smaller, so it is difficult to produce degradation of the silicon particles accompanied by the generation of irreversible capacity. The crystallite size of the silicon particles is calculated by the Scherrer formula based on the half-value width of the diffraction peak attributable to the Si (111) plane of the X-ray diffraction (XRD) pattern of the silicon particles.

[0033] As the negative electrode active material, LSX and carbon materials can also be used in combination. The volume of LSX expands and contracts with charging and discharging, so when its ratio in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode collector is likely to occur with charging and discharging. On the other hand, by using LSX and carbon materials in combination, the high capacity of silicon particles can be given to the negative electrode and excellent cycle characteristics can be achieved. The ratio of LSX in the total of LSX and carbon materials is preferably, for example, 3 to 30% by mass. As a result, it is easy to take into account both high capacity and improved cycle characteristics.

[0034] As the negative electrode current collector, metal foil, mesh, net, punched sheet, etc. can be used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc.

[0035] [positive electrode]

[0036] The positive electrode, for example, comprises a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry obtained by dispersing a positive electrode mixture in a dispersion medium on the surface of the positive electrode current collector and drying the slurry. The dried coating film can also be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode current collector or on both surfaces.

[0037] The positive electrode mixture contains a positive electrode active material as an essential component, and may contain a binder, a conductive agent, etc. as an optional component. The positive electrode active material contains a material that electrochemically absorbs and releases lithium ions. As a material that electrochemically absorbs and releases lithium ions, a layered compound containing a rock salt type crystal structure of lithium and a transition metal, a spinel compound containing lithium and a transition metal, a polyanion compound, etc. can be used. Among them, a layered compound is preferred.

[0038] Examples of the layered compound include Li a CoO2、Li a NiO2、Li a MnO2、Li a Co b Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni b M 1-b O c Among them, from the perspective of high capacity, lithium and nickel-containing general formula: Li a Ni b M 1-bThe composite oxide shown in Figure 2 is a composite oxide of 0.02. The more nickel there is in the composite oxide, the higher the basicity of the composite oxide is, and the reactivity with LFSI increases. In contrast, when isopropyl acetate is included in the electrolyte, the alkoxy radicals inhibit the reaction of LFSI, so the excessive reaction of LFSI is suppressed.

[0039] Here, M is a metal and / or semimetal other than Li and Ni, and satisfies 0.95≤a≤1.2 and 0.6≤b≤1. The value of a is the value of the positive electrode active material in a fully discharged state, and increases or decreases according to charge and discharge. From the perspective of obtaining a higher capacity, the above general formula preferably satisfies 0.8≤b≤1, and more preferably satisfies 0.9≤b<1 or 0.9≤b≤0.98.

[0040] M is not particularly limited, but is preferably at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Cu, Zn, Al, Cr, Pb, Sb, and B. M may be, for example, at least one selected from the group consisting of Mn, Fe, Co, Cu, Zn, and Al, and preferably contains at least one selected from the group consisting of Mn, Co, and Al.

[0041] As the positive electrode current collector, for example, a metal foil can be used, and examples of the material include stainless steel, aluminum, aluminum alloy, titanium, and the like.

[0042] As the binder of each electrode, resin materials can be exemplified, such as fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resins; polyimide resins such as polyimide and polyamide-imide; acrylic resins such as polyacrylic acid, polyacrylic acid salts (such as lithium polyacrylate), polymethyl acrylate, and ethylene-acrylic acid copolymers; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinyl pyrrolidone; polyether sulfone; rubber-like materials such as styrene-butadiene copolymer rubber (SBR), etc. These can be used alone or in combination of two or more. Among them, acrylic resins exert a high degree of bonding force relative to Si-containing materials.

[0043] It should be noted that the Si-containing material has a large expansion and contraction during charge and discharge, so the internal resistance is easy to increase and the cycle characteristics are also easy to decrease. In contrast, by using an acrylic resin in the binder and making the electrolyte contain LFSI, the increase in internal resistance and the decrease in cycle characteristics are greatly suppressed. This is because when the negative electrode containing an acrylic resin contains an electrolyte containing LFSI, the swelling of the acrylic resin is suppressed, the high binding force of the acrylic resin is maintained, and the increase in contact resistance between the negative electrode active material particles and between the negative electrode active material particles and the negative electrode collector is suppressed. For example, the acrylic resin can be less than 1.5 parts by mass per 100 parts by mass of the negative electrode active material, or it can be more than 0.4 parts by mass and less than 1.5 parts by mass.

[0044] Examples of the conductive agent include carbon blacks such as acetylene black, conductive fibers such as carbon fibers and metal fibers, carbon fluoride, metal powders such as aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and organic conductive materials such as phenylene derivatives. These may be used alone or in combination of two or more.

[0045] Examples of thickeners include carboxymethyl cellulose (CMC) and modified forms thereof (including salts such as Na salts), cellulose derivatives such as methyl cellulose (cellulose ethers, etc.), saponified polymers having vinyl acetate units such as polyvinyl alcohol, polyethers (polyalkylene oxides such as polyethylene oxide), etc. These may be used alone or in combination of two or more.

[0046] The dispersion medium is not particularly limited, and examples thereof include water, alcohol, and N-methyl-2-pyrrolidone (NMP).

[0047] [Electrolyte]

[0048] The electrolyte generally contains a lithium salt, a solvent and an additive. The electrolyte may contain various additives. Isopropyl acetate is classified as an additive. In the electrolyte, the total amount of the lithium salt and the solvent is more than 90% by mass of the electrolyte, and more preferably more than 95% by mass.

[0049] The solvent refers to cyclic carbonate, cyclic carboxylic acid ester, chain carbonate, chain carboxylic acid ester, and electrolyte components that are liquid at 25° C. and contain 3% by mass or more in the electrolyte. Any combination of one or more solvents may be used.

[0050] Examples of the cyclic carbonate include propylene carbonate (PC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), and vinylethylene carbonate (VEC).

[0051] Examples of the chain carbonate include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC).

[0052] Examples of the chain carboxylic acid ester include methyl formate, ethyl formate, methyl acetate, ethyl acetate, and methyl propionate. Among them, methyl acetate has low viscosity and high stability, and can improve the low-temperature characteristics of the battery. In addition, by using methyl acetate and isopropyl acetate in combination, the generation of gas due to the decomposition of methyl acetate tends to be suppressed. The content of methyl acetate in the electrolyte solution may be, for example, 3% by mass or more and 20% by mass or less.

[0053] Examples of the cyclic carboxylic acid ester include γ-butyrolactone (GBL) and γ-valerolactone (GVL).

[0054] It should be noted that a polymer that is solid alone at 25° C. is not included in the electrolyte solution components even if the content of the polymer in the electrolyte solution is 3% by mass or more. Such a polymer functions as a matrix for gelling the electrolyte solution.

[0055] Examples of the additive include carboxylic acids, alcohols, 1,3-propane sultone, methyl benzenesulfonate, cyclohexylbenzene, biphenyl, diphenyl ether, and fluorobenzene, in addition to 1,4-dioxane.

[0056] In addition to the lithium salts mentioned above, the electrolyte may also contain other salts. Examples of other salts include LiClO4, LiAlCl4, LiB 10 Cl 10 , LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, LiCl, LiBr, LiI, etc. Any combination of one or more lithium salts may be used.

[0057] [Separator]

[0058] It is ideal to sandwich a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, woven fabric, non-woven fabric, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.

[0059] As an example of the structure of a non-aqueous electrolyte secondary battery, an electrode group in which a positive electrode and a negative electrode are wound by means of a separator and a non-aqueous electrolyte is contained in an outer body can be cited. Alternatively, an electrode group of other types such as a stacked electrode group in which a positive electrode and a negative electrode are stacked by means of a separator can be used to replace the wound electrode group. The non-aqueous electrolyte secondary battery can be, for example, cylindrical, square, coin-shaped, button-shaped, laminated, etc.

[0060] Figure 1 This is a partially cutaway schematic perspective view of a square nonaqueous electrolyte secondary battery according to one embodiment of the present invention.

[0061] The battery comprises a square-bottomed battery case 4 and an electrode group 1 and a non-aqueous electrolyte (not shown) housed in the battery case 4. The electrode group 1 comprises a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator sandwiched therebetween. The electrode group 1 is formed by winding the negative electrode, the positive electrode, and the separator around a flat winding core and pulling out the winding core.

[0062] One end of the negative electrode lead 3 is mounted on the negative electrode collector of the negative electrode by welding or the like. One end of the positive electrode lead 2 is mounted on the positive electrode collector of the positive electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to the negative electrode terminal 6 provided on the sealing plate 5 by means of a gasket 7. The other end of the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive terminal. A resin frame is arranged on the upper part of the electrode group 1 to isolate the electrode group 1 from the sealing plate 5 and to isolate the negative electrode lead 3 from the battery case 4. The opening of the battery case 4 is sealed by the sealing plate 5.

[0063] The structure of the nonaqueous electrolyte secondary battery may be cylindrical, coin-shaped, button-shaped or the like having a metal battery case, or may be a laminated type battery having a battery case made of a laminate sheet which is a laminate of a barrier layer and a resin sheet.

[0064] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0065] <Examples 1 to 2 and Comparative Examples 1 to 4>

[0066] [Preparation of LSX]

[0067] Silicon dioxide and lithium carbonate were mixed in such a way that the atomic ratio Si / Li was 1.05, and the mixture was calcined in air at 950°C for 10 hours to obtain lithium silicate represented by the formula: Li2Si2O5 (u=0.5). The obtained lithium silicate was pulverized in such a way that the average particle size was 10 μm.

[0068] Lithium silicate (Li2Si2O5) with an average particle size of 10 μm and raw silicon (3N, average particle size of 10 μm) were mixed in a mass ratio of 45:55. The mixture was filled in a grinding cylinder (SUS, volume: 500 mL) of a planetary ball mill (Fritsch, P-5), 24 SUS balls (diameter 20 mm) were placed in the grinding cylinder and the lid was closed, and the mixture was pulverized at 200 rpm for 50 hours in an inert atmosphere.

[0069] Next, the powdered mixture was taken out in an inert atmosphere, and fired at 800° C. for 4 hours in the inert atmosphere while being pressed by a hot press, thereby obtaining a sintered body (LSX) of the mixture.

[0070] After that, the LSX was crushed and passed through a 40 μm sieve, and the obtained LSX particles were mixed with coal tar (MCP250 manufactured by JFE Chemical Industry Co., Ltd.), and the mixture was calcined at 800° C. in an inert atmosphere, so that the surface of the LSX particles was covered with conductive carbon to form a conductive layer. The coating amount of the conductive layer was set to 5% by mass relative to the total mass of the LSX particles and the conductive layer. Then, LSX particles with an average particle size of 5 μm having a conductive layer were obtained using a sieve.

[0071] [Production of negative electrode]

[0072] LSX particles with a conductive layer and graphite were mixed at a mass ratio of 6:94 and used as negative electrode active materials. The negative electrode active material, lithium polyacrylate and styrene-butadiene rubber (SBR) were mixed at a mass ratio of 97.5:1:1.5, and after adding water, a mixer (manufactured by PRIMIX Corporation, TKHIVIS MIX) was used to stir and prepare negative electrode slurry. Next, the negative electrode slurry was applied to the surface of the copper foil, and the coating was dried and then rolled to form a 1.5 g / cm2 film on both sides of the copper foil. 3 The negative electrode of the negative electrode mixture layer.

[0073] [Production of positive electrode]

[0074] Lithium nickel composite oxide (LiNi 0.8 Co 0.18 Al 0.02 O2), acetylene black and polyvinylidene fluoride were mixed, N-methyl-2-pyrrolidone (NMP) was added, and a mixer (manufactured by PRIMIX Corporation, TKHIVIS MIX) was used to stir to prepare a positive electrode slurry. Next, the positive electrode slurry was applied to the surface of the aluminum foil, and the coating was dried and then rolled to form a 3.6 g / cm2 film on both sides of the aluminum foil. 3 The positive electrode of the positive electrode mixture layer.

[0075] [Preparation of non-aqueous electrolyte]

[0076] The solvent used was a mixed solvent containing ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and methyl acetate (MA) in a volume ratio of 20:5:55:20. LFSI and LiPF6 were dissolved in the mixed solvent in the proportion shown in Table 1. In addition, the electrolyte contained isopropyl acetate in the content shown in Table 1.

[0077] [Fabrication of non-aqueous electrolyte secondary battery]

[0078] The electrode group was prepared by installing a tab on each electrode, and the positive electrode and the negative electrode were wound into a spiral shape with the tab located at the outermost periphery with the aid of a separator. The electrode group was inserted into an outer casing made of an aluminum laminate film, vacuum dried at 105° C. for 2 hours, and then injected with a nonaqueous electrolyte. The opening of the outer casing was sealed to obtain batteries A1 to A2 of Examples 1 to 2 and batteries B1 to B4 of Comparative Examples 1 to 4.

[0079] [evaluate]

[0080] Each battery after fabrication was charged at a constant current of 0.3 It (800 mA) at 45°C until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 0.015 It (40 mA). Thereafter, the battery was discharged at a constant current of 0.3 It (800 mA) until the voltage reached 2.75 V.

[0081] The rest period between charge and discharge was set to 20 minutes, and the charge and discharge cycle was repeated 300 times under the above charge and discharge conditions. The ratio of the discharge capacity of the 300th cycle to the discharge capacity of the first cycle was calculated as the capacity retention rate. The results are shown in Table 1.

[0082] After 300 cycles, the batteries were taken out and disassembled, and the components of the electrolyte were analyzed by gas chromatography-mass spectrometry (GCMS). The results confirmed the presence of isopropyl acetate in the electrolytes of batteries A1, A2, B2, and B4.

[0083] The measurement conditions of GCMS used for the analysis of the electrolyte solution are as follows.

[0084] Device: Shimadzu Corporation, GC17A, GCMS-QP5050A

[0085] Column: Agilent technologies, inc., HP-1 (film thickness 1.0 μm × length 60 m)

[0086] Column temperature: 50℃→110℃(5℃ / min, 12 minutes hold)→250℃(5℃ / min, 7 minutes hold)→300℃(10℃ / min, 20 minutes hold)

[0087] Split ratio: 1 / 50

[0088] Line speed: 29.2cm / s

[0089] Inlet temperature: 270℃

[0090] Injection volume: 0.5 μL

[0091] Interface temperature: 230℃

[0092] Mass range: m / z = 60 ~ 100 (SCAN mode)

[0093] [Table 1]

[0094]

[0095] Industrial Applicability

[0096] According to the present invention, a nonaqueous electrolyte secondary battery having excellent long-term cycle characteristics can be provided. The nonaqueous electrolyte secondary battery of the present invention is useful as a main power source for mobile communication devices, portable electronic devices, and the like.

[0097] Description of Reference Numerals

[0098] 1 Electrode set

[0099] 2 Positive lead

[0100] 3 Negative lead

[0101] 4 Battery housing

[0102] 5 Sealing plate

[0103] 6 Negative terminal

[0104] 7 Gasket

Claims

1. A non-aqueous electrolyte secondary battery comprising: a positive electrode, a negative electrode and an electrolyte, The electrolyte comprises lithium salt and isopropyl acetate, The lithium salt comprises lithium bis(fluorosulfonyl)imide, The content of the isopropyl acetate in the electrolyte is 50 ppm or more and 1000 ppm or less relative to the mass of the electrolyte, The lithium salt further comprises LiPF6, The electrolyte solution contains methyl acetate, and a content of methyl acetate in the electrolyte solution is 3 mass % or more and 20 mass % or less.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The ratio of the lithium bis(fluorosulfonyl)imide in the lithium salt is 1 mol % or more and 60 mol % or less.

3. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The concentration of the lithium salt in the electrolyte solution is 1 mol / liter or more and 2 mol / liter or less.

4. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The positive electrode contains a composite oxide containing lithium and nickel, The composite oxide is of the general formula: Li a Ni b M 1-b A layered compound with a rock salt crystal structure as shown in O2, M is a metal and / or semimetal other than Li and Ni, It satisfies 0.95≤a≤1.2 and 0.6≤b≤1.

5. An electrolyte for a non-aqueous electrolyte secondary battery, comprising a lithium salt and isopropyl acetate, The lithium salt comprises lithium bis(fluorosulfonyl)imide, The content of the isopropyl acetate is 50 ppm or more and 200 ppm or less in terms of mass ratio, The lithium salt further comprises LiPF6, The electrolyte solution contains methyl acetate, and a content of methyl acetate in the electrolyte solution is 3 mass % or more and 20 mass % or less.

Citation Information

Patent Citations

  • Nonaqueous electrolyte solution and nonaqueous electrolyte battery using same

    WO2014157591A1

  • Non-aqueous electrolyte solution and electricity storage device in which same is used

    WO2016009994A1

  • Method for manufacturing electrolyte material

    CN107112591A

  • Nonaqueous electrolyte solution and nonaqueous electrolyte solution cell using it

    JP2008198409A

  • Nonaqueous lithium battery and application method thereof

    JP2017021949A